Soil Nitrogen Leaching in Logged Beetle‐Killed Forests and Implications for Riparian Fuel Reduction. Issue 2 (1st March 2019) - Rhoades, Charles C.
Abstract : Recent extensive forest mortality and subsequent salvage logging may threaten the water supply from headwater catchments in western North America. Land managers confronting current insect outbreaks and projected increases in forest disturbance require information about the potential water quality consequences of these changes. This study is a hillslope‐scale evaluation of soil N and C leaching in lodgepole pine forests that have experienced 80% overstory tree mortality. I measured extractable inorganic and ion resin exchangeable‐N forms, in situ net mineralization and nitrification, and leaching in upland and riparian forests with the following treatment combinations: (i) uncut upland with uncut riparian, (ii) harvested upland with uncut riparian buffer, and (iii) harvested upland with harvested riparian. This design permitted comparison of N cycling and leaching in 30‐m‐wide riparian buffers and a riparian fuel break designed to remove canopy fuels and reduce wildfire concerns in areas with extensive bark beetle infestation. Harvesting increased NO3 –N, total dissolved N, and dissolved organic C leachate concentrations in upland landscapes but had little effect on net N transformations. Leachate N and C concentrations were 1.5 times higher in riparian buffers downslope of harvested uplands than those in riparian zones downslope of uncut uplands. Riparian forest harvest increased N leaching relative to uncut buffers, although postharvest concentrations remained well below regional water quality standards. Thus, while this study provides evidence that N leaching from dead buffers is low, it also suggests that riparian fuel reduction may complement wildfire mitigation objectives without compromising watershed protection. Core Ideas: Nitrogen leaching was low in riparian buffers even though most trees were dead. Harvest of dead riparian forest increased N losses, but concentration remained low. Novel riparian management may achieve both wildfire mitigation and watershed protection.